Cabazitaxel activity in men with metastatic castration-resistant prostate cancer with and without DNA damage repair defects. (December 2021) - Aldea, Mihaela; Lam, Laurent; Orillard, Emeline; Llacer Perez, Casilda; Saint-Ghislain, Mathilde; Gravis, Gwenaelle; Fléchon, Aude; Roubaud, Guilhem; Barthelemy, Philippe; Ricci, Francesco; Priou, Frank; Neviere, Zoe; et al.
Abstract: Background: Cabazitaxel was shown to improve overall survival (OS) in patients with metastatic castration-resistant prostate cancer (mCRPC) after abiraterone/enzalutamine and docetaxel failure, though benefit by the presence of DNA damage repair (DDR) defects is unknown. With the advent of poly(adenosine diphosphate–ribose) polymerase inhibitors (PARPi) in partially overlapping indications with cabazitaxel, we aimed to determine cabazitaxel activity in men with mCRPC according to their DDR status. Methods: This is a retrospective multicenter study that enrolled patients with mCRPC treated with cabazitaxel who had undergone DDR tumour tissue profiling. Patients with at least one deleterious germline or somatic alterations were considered DDR positive (DDR+). Each DDR + patient has been matched with a DDR negative (DDR-) from the same institution who underwent the same test. An exploratory cohort of patients found to be DDR + by liquid biopsy was also included. Prostate specific antigen (PSA) decline≥50% (PSA50), PSA progression-free survival (PFS, PSA-PFS), radiographic PFS (rPFS), clinical PFS or radiographic PFS (c/rPFS) and OS were evaluated. Results: Among 190 men (95 DDR+, 95 DDR-) with tissue sequencing, PSA50 was achieved with cabazitaxel in 29/92 (32%) and 33/92 (36%) in patients with DDR+ and DDR- ( P = 0.64 ). The median rPFS was 5.33 months [95%CI 4.34–7.04] versus 5.75 months [95%CI 4.67–7.27] ( P = 0.55 ). The median OS was 15.4 months [95%CI 12.16–26.6] and 11.5 months [95%CI 9.76–14.4] ( P = 0.036 ), respectively. No PSA50 responses on cabazitaxel were observed in BRCA1/2 patients previously treated with PARPi (n = 10). Similar outcomes with cabazitaxel were observed in the liquid biopsy cohort (n = 63 DDR+). Conclusions: Our study suggests that cabazitaxel is active in patients with mCRPC regardless of their DDR status, although its activity in men pretreated with a PARPi may be lower. Highlights: Cabazitaxel is active in patients with metastatic castration resistant prostate cancer, regardless of the DNA damage repair status. Overall survival was higher in DNA damage repair + men treated with cabazitaxel. Efficacy of cabazitaxel may be lower in men previously treated with a poly(adenosine diphosphate–ribose) polymerase inhibitors.